Admission hyperglycemia and adverse outcomes in diabetic and non-diabetic patients with non-ST-elevation myocardial infarction undergoing percutaneous coronary intervention. Issue 1 (December 2017) - Hao, Yuanyuan; Lu, Qun; Li, Tao; Yang, Guodong; Hu, Peijing; Ma, Aiqun
Abstract Background The association between admission hyperglycemia and adverse outcomes in patients with non-ST-segment elevation myocardial infarction (NSTEMI) undergoing percutaneous coronary intervention (PCI) has not been well studied, and the optimal plasma glucose cut-off values for prognosis for NSTEMI patients with and without diabetes have not been determined. Methods According to glucose level and diabetes status, consecutive NSTEMI patients undergoing PCI (n  = 890) were divided into four groups: without diabetes mellitus (DM) and admission plasma glucose (APG) <144 or ≥144 mg/dL; or with DM and APG <180 or ≥180 mg/dL. All patients were followed up at 30 days and 3 years after discharge, and the outcomes were assessed. Results Admission hyperglycemia was found in 44 and 28% of the DM and non-DM patients, respectively. Multivariable analyses showed that the APG level was an independent predictor of 30-day and 3-year MACEs. Receiver operating characteristic curve analysis revealed that the appropriate cut-off values were 178 and 145 mg/dL for patients with and without DM, respectively, or 157 mg/dL for all patients. Conclusions Admission hyperglycemia may be used to predict 30-day and 3-year MACEs in patients with NSTEMI undergoing PCI, irrespective of diabetes status. However, the optimal admission glucose cut-off values for predicting prognosis differ for patients with or without DM.